Business Coaching to Develop Hi Kuliner Production Processes through Business Model Innovation - Indriyani, Marlina Ririn (International Journal of Social Service and Research, 2023)
Small and Medium Enterprises (MSMEs) in the Indonesian economy have been recognized as having a role in both absorbing labor and contributing to the Gross Domestic Product (GDP). However, MSMEs often face challenges in fundamental business aspects, such as planning, management, business models, innovation and business processes. This case study examines MSME assistance in Indonesia using internal VRIO analysis, Market Segmentation, external PEST analysis, Porter's Five Forces, Business Model Canvas, and SWOT to identify business model improvements, especially in key activity blocks. The research results emphasize the importance of developing and updating key activities that are in line with the MSME business.